A Cross-Sectional Study to Assess the Determinants of Protein Energy Malnutrition Among Tribal Pre- School Children: a Case Study of Barjora & Chatna Block, Bankura District In West Bengal, India: Exploring the Prevalence and Determinants of Protein Energy Malnutrition in Rural Tribal Pre-School Children: A Case Study in West Bengal, India (Journal of Advances and Scholarly Researches in Allied Education, 2015)
In new millennium India faces burden of diseases, like Protein EnergyMalnutrition (PEM). UNICEF (2008) estimated that 146 million children wereunderweight in the developing world. India accounts for 57 million of them. Theobjectives were to assess the prevalence of PEM among preschool children and toassociate the selected socio demographic variables with prevalence of PEM.Cross sectional descriptive design with simple random sampling was used toselect two blocks from Bankura district in West Bengal. Totally 1501 childrenaged between 3-5 years were assessed. The prevalence of underweight wassignificantly higher in children at 3 years than 4 & 5 years of age.Totally 50% of them were underweight, 32% stunted, 37% wasted and 23% withimpaired mid arm circumference. There was significant association between ageand sex of the children with PEM at the level of P